2011
DOI: 10.1002/lt.22261
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Prevalence and significance of occult hepatitis B in a liver transplant population with chronic hepatitis C

Abstract: (page 534): Explant-proven hepatocellular carcinoma (HCC) was found in 13 of 22 (59%) patients with occult HBV liver compared to 8 of 22 (36%) patients without occult HBV liver (P ¼ 0.36, odds ratio 2.5; confidence interval 0.76-8.54.On page 536, column 2: On univariate analysis, no significant differences were noted between the two groups in terms of MELD score at entry, or explant-proven HCC.On page 536, column 2: Occult HBV liver was not associated with the presence of explant-proven HCC. Of 22 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Kannangai et al29 detected HBV DNA in the livers of three of 19 (16%) HBsAg‐negative patients in the United States; only five of the 19 were infected with hepatitis C. Shetty et al30 found HBV DNA in the livers of 13 of 21 (62%) patients with HCV‐related HCC and 9 of 23 (39%) patients with HCV‐related cirrhosis and no HCC. An erratum published by Shetty concluded that occult HBV was not associated with HCC ( P = 0.36) 31. Our study differs from these three studies in that very small samples from liver biopsies rather than surgically resected tumors or explant livers were available for testing for HBV DNA.…”
Section: Discussionmentioning
confidence: 72%
“…Kannangai et al29 detected HBV DNA in the livers of three of 19 (16%) HBsAg‐negative patients in the United States; only five of the 19 were infected with hepatitis C. Shetty et al30 found HBV DNA in the livers of 13 of 21 (62%) patients with HCV‐related HCC and 9 of 23 (39%) patients with HCV‐related cirrhosis and no HCC. An erratum published by Shetty concluded that occult HBV was not associated with HCC ( P = 0.36) 31. Our study differs from these three studies in that very small samples from liver biopsies rather than surgically resected tumors or explant livers were available for testing for HBV DNA.…”
Section: Discussionmentioning
confidence: 72%
“…Unfortunately, the authors of that meta‐analysis may not have been aware of an erratum that was published by Shetty et al . in 2011 in which those authors reported numerous errors in their 2008 paper leading to a corrected nonsignificant odds ratio of 2.5 (95% CI, 0.76–8.54) and a P value of 0.36 instead of 0.04. This led Shetty and colleagues to reverse their original conclusion stating that they now found no association between the presence of occult HBV and the development of explant‐proven HCC.…”
Section: An Analysis Of the Association Of Occult Hepatitis B And Hccmentioning
confidence: 99%
“…This conclusion is similar to that reported in a meta-analysis by Shi et al [27] in which OHB appeared to be a cofactor or precipitating event in the development of HCC in prospectively followed, HCV-coinfected populations, whereas HCC risk in the non-HCVinfected cohorts was more directly attributed to the OHB infection. Unfortunately, the authors of that meta-analysis may not have been aware of an erratum that was published by Shetty et al in 2011 [67] in which those authors reported numerous errors in their 2008 paper leading to a corrected nonsignificant odds ratio of 2.5 (95% CI, 0.76-8.54) and a P value of 0.36 instead of 0.04. This led Shetty and colleagues to reverse their original conclusion stating that they now found no association between the presence of occult HBV and the development of explantproven HCC.…”
Section: An Analysis Of the Association Of Occult Hepatitis B And Hccmentioning
confidence: 99%